Role of oxygen and boron to control the duality behavior and thermal stability in Boron doped amorphous indium-zinc-oxide thin films. (9th April 2019) - Kumar, Naveen; Arora, Kanika; Kumar, Mukesh
Abstract: Carrier suppression without deteriorating the carrier mobility is a key challenge in metal like carrier density of amorphous transparent conducting oxide (TCO) thin films for next-generation flexible optoelectronic device applications. Here, we studied the role of oxygen for confining the behavior of boron dopant as a carrier suppressor and as a carrier donor in amorphous indium-zinc-oxide (a-IZO) thin films. The carrier density of amorphous IZO thin film was reduced to the order of ∼10 16 cm −3 with carrier mobility of ∼9 cm 2 /Vs by precisely controlling the boron and oxygen content in BIZO thin films. The electrical properties revealed that boron requires an extra presence of oxygen to activate its carrier suppressant nature. Structural and defects chemistry in IZO and BIZO thin films were studied by X-ray diffraction (XRD), Photoluminescence (PL) and X-ray photoelectron spectroscopy (XPS). The XRD confirmed the amorphous nature of IZO and BIZO while PL and XPS results suggested the presence of less defects in BIZO in contrast to the IZO films, which is a prerequisite criterion to choose the oxide thin film for transistors and fast switching device applications. The post deposition annealing of IZO and BIZO thin film in air confirmed the better thermal stability of BIZO over IZO thin film. In the perspective of experimental verification, the photo-persistent current with time measurement showed a relevant evidence of less concentration of oxygen vacancies in BIZO thin films by exhibiting the small decay time as compared to IZO thin films. This study proposes the appropriate use of B as a carrier donor and a carrier suppressor in IZO matrix as a robust, reliable and thermally stable active layer for next-generation flexible and stable electronic device applications.